Implementasi Nilai-Nilai Kearifan Lokal Siswa Kelas X Melalui Gerakan Literasi Sekolah pada Proyek Penguatan Profil Pelajar Pancasila (P5) Di SMA Negeri 1 Purwareja Klampok - Karmelita, Linovia (UM Purwokerto Press, 2024)
Project-based learning to strengthen the Pancasila Student Profile (P5) is a learning method that uses projects or activities as a means of communication. Project-based learning for the Pancasila student profile includes seven themes, one of which is local wisdom. The values of local wisdom are values that are preserved, applied in people's daily lives and passed on to the next generation. SMA Negeri 1 Purwareja Klampok made a program to unite P5 with the school literacy program, producing 10 books by students with the theme of local wisdom. The purpose of this research is to dissect the values of local wisdom in the poetry anthology Senja di Gudang Sastra. The research method uses a descriptive form of leatherative method with a literary anthropology approach. The results of the study resulted in 4 values, namely religious values containing belief in God, self-awareness to be grateful for God's blessings; aesthetic values contain the context of cultural arts related to the beauty of a work of art, with indicators being customs, indicators of obedience, indicators of natural and cultural resources; mutual cooperation values reflect cooperative actions to help each other carried out by more than two people together with the same goal; and moral values reflect the nature of individuals who are helpful, have compassion, are friendly and polite.